Improved Performance of Four Switch Three Phase with SEPIC-Based Inverter - Prabu B; Murugan M (Institute of Advanced Engineering and Science, 2016)
The proposed novel four-switch three-phase (FSTP) inverter is to design to reduce the rate, difficulty, mass, and switching losses of the DC-AC conversion system. Here the output line voltage cannot exceed half the input voltage in the out-dated FSTP inverter and it operates at half the DC input voltage. Single-Ended Primary-Inductance Converter (SEPIC) is a novel design for the FSTP inverter proposed in this paper. In this proposed topology the necessity of output filters is not necessary for the pure sinusoidal output voltage. Related to out-dated FSTP inverter, the proposed FSTP SEPIC inverter raises the voltage utilization aspect of the input DC supply, where the suggested topology delivers the higher output line voltage which can be extended up to the full value of the DC input voltage. In the proposed topology a control used called the integral sliding-mode (ISM) control and this control is used to enhance its dynamics and to ensure strength of the system during different operating conditions. Simulation model and results are used to authorise the proposed concept and simulations results show the effectiveness of the proposed inverter.